The legal adjusting of leasing companies about current legistation of Ukraine - Ментух, Наталія Фелікіссімівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The issue of legal status of leasing company as a basic participant of leasing activity without which isimpossible the normal functioning of leasing process which can satisfy needs with leasing services and towhich nowadays is observed popularity in science of commerce law.